Assessment of axial bone rigidity inrats with metabolic diseases using CT-based structural rigidity analysis. Issue 2 (February 2012) - Smith, M. D.; Baldassarri, S.; Anez-Bustillos, L.; Tseng, A.; Entezari, V.; Zurakowski, D.; Snyder, B. D.; Nazarian, A.
Abstract : Objectives: This study aims to assess the correlation of CT-based structuralrigidity analysis with mechanically determined axial rigidity innormal and metabolically diseased rat bone. Methods: A total of 30 rats were divided equally into normal, ovariectomized, and partially nephrectomized groups. Cortical and trabecular bonesegments from each animal underwent micro-CT to assess their averageand minimum axial rigidities using structural rigidity analysis.Following imaging, all specimens were subjected to uniaxial compressionand assessment of mechanically-derived axial rigidity. Results: The average structural rigidity-based axial rigidity was wellcorrelated with the average mechanically-derived axial rigidityresults (R 2 = 0.74). This correlation improved significantly(p < 0.0001) when the CT-based Structural Rigidity Analysis (CTRA)minimum axial rigidity was correlated to the mechanically-derivedminimum axial rigidity results (R 2  = 0.84). Tests ofslopes in the mixed model regression analysis indicated a significantlysteeper slope for the average axial rigidity compared with the minimumaxial rigidity (p = 0.028) and a significant difference in the intercepts(p = 0.022). The CTRA average and minimum axial rigidities werecorrelated with the mechanically-derived average and minimum axialrigidities using paired t -test analysis (p = 0.37and p = 0.18, respectively). Conclusions: In summary, the results of this study suggest that structuralrigidity analysis of micro-CT data can be used to accurately andquantitatively measure the axial rigidity of bones with metabolicpathologies in an experimental rat model. It appears that minimumaxial rigidity is a better model for measuring bone rigidity thanaverage axial rigidity.